Antioxidant Systematic Alteration Was Responsible for Injuries Inflicted on the Marine Blue Mussel Mytilus edulis Following Strontium Exposure - Zihua Cheng; Mengxue Xu; Qiyue Cao; Wendan Chi; Sai Cao; Zhongyuan Zhou; You Wang (MDPI AG, 2024)
The ionic properties of strontium (Sr), a significant artificial radionuclide in the marine environment, were estimated using a stable nuclide-substituting experimental system under controlled laboratory conditions. The bio-accumulation of Sr and its impacts, as well as any possible hidden mechanisms, were evaluated based on the physiological alterations of the sentinel blue mussel Mytilus edulis. The mussels were exposed to a series of stress-inducing concentrations, with the highest solubility being 0.2 g/L. No acute lethality was observed during the experiment, but sublethal damage was evident. Sr accumulated in a tissue-specific way, and hemolymph was the target, with the highest accumulating concentration being 64.46 µg/g wet weight (ww). At the molecular level, increases in the levels of reactive oxygen species (ROS) and malondialdehyde (MDA) and changes in ROS components (H2O2, O2−, and -OH) and antioxidant system activity indicated that the redox equilibrium state in hemocytes was disturbed. Furthermore, the rise in the hemocyte micronucleus (MN) rate (4‰ in the high-concentration group) implied DNA damage. At the cellular level, the structures of hemocytes were damaged, especially with respect to lysosomes, which play a crucial role in phagocytosis. Lysosomal membrane stability (LMS) was also affected, and both acid phosphatase (ACP) and alkaline phosphatase (AKP) activities were reduced, resulting in a significant decline in phagocytosis. The hemolymph population structure at the organ level was disturbed, with large changes in hemocyte number and mortality rate, along with changes in component ratios. These toxic effects were evaluated by employing the adverse outcome pathway (AOP) framework. The results suggested that the disruption of intracellular redox homeostasis is a possible explanation for Sr-induced toxicity in M. edulis.